Influence of Biologically Inert Protective Coating Based on Pectin Substances on PUFA Quality and Shelf-Life of Frozen Fish - A. Gerasim; S. Patyukov; N. Patyukova (Holodilʹnaâ Tehnika i Tehnologiâ, 2018)
The influence of a biologically inert protective coating on the basis of low-esterified pectin substances (LEPS) on the qualitative indicators of frozen fish and its lipids is studied in this paper: organoleptic, physico-chemical, structural-mechanical and biochemical changes in fish of various methods of freezing during 240 days of cold storage. The limiting periods of storage of a silver carp (Hypophthalmichthys molitrix) of different ways of freezing are established. The prolongation of the shelf life of refrigeration and the higher quality indices of frozen fish with the use of a protective coating based on low-esterified pectin substances is due to the reduction of shrinkage and inhibition of hydrolytic decomposition and oxidative damage of lipids by preventing the contact of the surface of frozen fish with oxygen in the air. In addition, when freezing fish in a calcium chloride solution, the LEPS-based coatings exhibit barrier properties, preventing the diffusion of calcium ions into the muscle tissue of the product. Such a mechanism of influence on the duration of fish storage of various methods of freezing during prolonged cold storage allows to obtain frozen fish with high quality indices and to substantially reduce losses during refrigerated storage.